Measurement of the effective Bs0→K+K- lifetime - Aaij, R; Abellan Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Alkhazov, G; Alvarez Cartelle, P; et al. (2012)
A measurement of the effective Bs0→K+K- lifetime is presented using approximately 37pb -1 of data collected by LHCb during 2010. This quantity can be used to put constraints on contributions from processes beyond the Standard Model in the Bs0 meson system and is determined by two complementary approaches asτKK=1.440±0.096(stat)±0.008(syst)±0.003(model)ps. © 2011 CERN.